2014
DOI: 10.1038/tp.2014.17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic antipsychotic treatment on striatal phosphodiesterase 10A levels: a [11C]MP-10 PET rodent imaging study with ex vivo confirmation

Abstract: A number of phosphodiesterase 10A (PDE10) inhibitors are about to undergo clinical evaluation for their efficacy in treating schizophrenia. As phosphodiesterases are in the same signalling pathway as dopamine D2 receptors, it is possible that prior antipsychotic treatment could influence these enzyme systems in patients. Chronic, in contrast to acute, antipsychotic treatment has been reported to increase brain PDE10A levels in rodents. The aim of this study was to confirm these findings in a manner that can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…However, previous studies of the effect of antipsychotics on PDE10A availability conflict with one study reporting an increase of PDE10A in rats exposed to both haloperidol and clozapine, 42 whereas Natesan et al observed no difference in PDE10A availability after chronic haloperidol administration to rats. 10 The latter concurs with a recent non-human primate study that did not detect any significant changes from haloperidol treatment. 43 It is not fully clear if clozapine and the other diazepines (olanzapine and quetiapine) that the patients were treated with in our study are D 1 agonists or antagonists, but a reasonable amount of data is pointing towards clozapine being a D 1 agonist as reviewed by Ahlenius et al…”
Section: Strengths and Limitationssupporting
confidence: 88%
See 1 more Smart Citation
“…However, previous studies of the effect of antipsychotics on PDE10A availability conflict with one study reporting an increase of PDE10A in rats exposed to both haloperidol and clozapine, 42 whereas Natesan et al observed no difference in PDE10A availability after chronic haloperidol administration to rats. 10 The latter concurs with a recent non-human primate study that did not detect any significant changes from haloperidol treatment. 43 It is not fully clear if clozapine and the other diazepines (olanzapine and quetiapine) that the patients were treated with in our study are D 1 agonists or antagonists, but a reasonable amount of data is pointing towards clozapine being a D 1 agonist as reviewed by Ahlenius et al…”
Section: Strengths and Limitationssupporting
confidence: 88%
“…7 PDE10A has opposing effects on the output from these striatal pathways by regulating second messenger cascades, and inhibition of PDE10A does indeed seem to reduce positive and in some studies also negative symptoms in animal models of schizophrenia. [8][9][10][11][12] Moreover, patients with other striatal disorders, such as Parkinson's and Huntington's disease, have lower availability of striatal PDE10A early in the disease course. 13,14 Although PDE10A inhibition has shown promise as a novel target of the treatment of schizophrenia, 15 recently the first positron emission tomography (PET) study of PDE10A expression in patients with schizophrenia found no difference compared to healthy controls using the [ 11 C]IMA107 ligand.…”
Section: Introductionmentioning
confidence: 99%
“…; Natesan et al . ). Despite the growing interest in PDE10A, little is known about the regulation of PDE10A enzymatic activity.…”
Section: Discussionmentioning
confidence: 97%
“…; Hebb & Robertson ; Natesan et al . ; Xu et al . ), and haloperidol or clozapine treatment increases Pde10a expression (Xu et al .…”
mentioning
confidence: 99%